Puerperal ventral epidural hematoma after epidural labor analgesia. (May 2017) - Gruzman, I.; Shelef, I.; Weintraub, A.Y.; Zlotnik, A.; Erez, O.
Highlights: Epidural hematoma is a rare complication of obstetrical neuraxial anesthesia. Common symptoms are backache, hyperesthesia and muscle spasm. Severe symptoms such as skin anesthesia, rectal or bladder paresis also occur. Delayed onset of symptoms and 'foot drop' are possible. Spontaneous resolution, with or without steroid therapy, is possible. Abstract: Serious complications in obstetric anesthesia are a rare occurrence. High neuraxial block, respiratory arrest in labor and delivery, and an unrecognized spinal catheter are among the most frequently reported serious complications. A serious complication occurs in approximately 1:3 000 obstetric patients. Neuraxial hematoma after obstetric epidural analgesia or anesthesia is extremely rare. We present a case of a puerperal spinal epidural hematoma following epidural labor analgesia. The patient presented with foot drop, which resolved after conservative treatment. We reviewed the epidemiology, clinical manifestations and treatment options for this rare complication.